Screening of Surface-Exposed Lipoproteins of Leptospira Involved in Modulation of Host Innate Immune Response - Kumar, Ajay; Varma, Vivek P.; Faisal, Syed M. (Frontiers in Microbiology, 2022)
Leptospira, a zoonotic pathogen, is capable of causing both chronic and acute infection in a susceptible host. Surface-exposed lipoproteins play a major role in modulating the host immune response by activating the innate cells like macrophages and dendritic cells or evading complement attack and killing by phagocytes like neutrophils to favor pathogenesis and establish infection. In this study, we screened some surface-exposed lipoproteins known to be involved in pathogenesis to assess their possible role in immune modulation (innate immune activation or evasion). Surface proteins of the Len family (LenB, LenD, and LenE), Lsa30, Loa22, and Lipl21 were purified in recombinant form and then tested for their ability to activate macrophages of the different host (mouse, human, and bovine). These proteins were tested for binding with complement regulators like Factor H (FH), C4 Binding Protein (C4BP), and host protease Plasminogen (PLG) and also as nucleases to access their possible role in innate immune evasion. Our results show that, of various proteins tested, Loa22 induced strong innate activation and Lsa30 was least stimulatory, as evident from the production of pro-inflammatory cytokines (interleukin-6 and tumor necrosis factor–α) and expression of surface markers [CD80, CD86, and major histocompatibility complex class II (MHCII)]. All the tested proteins were able to bind to FH, C4BP, and PLG; however, Loa22 showed strong binding to PLG correlating to plasmin activity. All the proteins except Loa22 showed nuclease activity, albeit with a requirement of different metal ions. The nuclease activity of these proteins correlated to in vitro degradation of neutrophil extracellular trap (NET). In conclusion, our results indicate that these surface proteins are involved in innate immune modulation and may play a critical role in assisting the bacteria in invading and colonizing the host tissue for persistent infection.